PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL GURU TERHADAP PRESTASI BELAJAR SISWA (Studi Empirik Penilaian Terhadap Guru Oleh Siswa Kelas XII Akuntansi Di Sekolah Menengah Kejuruan Kota Tangerang) - Mulyanto, Sigit (Jurnal Aplikasi Manajemen Pendidikan, 2015)
The purpose of this research is to analyze the influence of intelectual intelligence, emotional intelligence, and teacher spiritual intelligencetoward student’s achievement.This research was done at two Vocational High School for accountancy in Tangerang. Methods usedbyresearchersin the selection ofthe study samplewaspurposivesampling.The statistics method that’s used is multiple regression analyze.The result of this research show by simultaneos, there is analyze significant influence between intelectual intelligence, emotional intelligence, and teacher spiritual intelligence variable that’s had teacher with student’s achievement level.Intelectual intelligence,teacher spiritual intelligence variable that’s had teacher influence to student’s achievement level, and emotional intelligence no effect tostudent’s achievement level.